Cystic fibrosis screen positive, inconclusive diagnosis. Issue 6 (November 2016) - Barben, Jürg; Southern, Kevin W.
Abstract : Purpose of review: A challenging sequelae of newborn bloodspot screening (NBS) for cystic fibrosis (CF) has been the identification of infants with an unclear diagnosis after a positive NBS result, which leads to uncertainty for healthcare professionals and families. This review describes the classification, frequency, clinical outcome and early management of these infants. Recent findings: In the US, infants with an inconclusive diagnosis after NBS are labelled 'CF transmembrane conductance regulator (CFTR)-related metabolic syndrome' (CRMS), and in Europe 'CF screen positive, inconclusive diagnosis' (CFSPID). According to recent studies, the majority of CRMS/CFSPID infants will remain well and have no long-term health implications. CRMS/CFSPID infants are at risk of developing CFTR-related disorder or atypical CF, with clinical features of CF but normal or intermediate sweat chloride values. Summary: The frequency of CRMS/CFSPID is more than anticipated, relating to the increased use of screening algorithms that employ extended gene sequencing. The terms CRMS and CFSPID are interchangeable and there has been an international effort to harmonise the designation to CRMS/CFSPID. With clearer designation criteria, long-term data will be collected on outcomes that will guide management strategies.